International Perspectives on Contemporary Democracy - Nardulli, Peter F. (Book collections on Project MUSE., 2008)
Democracy enjoys unparalleled prestige at the beginning of the twenty-first century as a form of government. Some of the world's most prosperous nations are democracies, and an array of nations in Europe, Africa, and South America have adopted the system. This globalization has also met resistance and provoked concerns about international power exerted by institutions and elites that are beyond the control of existing democratic institutions. In this volume, leading scholars of democracy engage the key questions about how far and how fast democracy can spread, and how international agencies and international cooperation uneasily affect national democracies. At first glance, the efforts of intergovernmental organizations to intervene in a nation's governance seem anything but democratic to that nation. The contributors demonstrate why democracy has been so attractive and so successful, but are also candid about what limits it may reach, and why._x000B__x000B_Contributors are Lisa Anderson, Larry Diamond, Zachary Elkins, John R. Freeman, Brian J. Gaines, James H. Kuklinski, Peter F. Nardulli, Melissa A. Orlie, Buddy Peyton, Paul J. Quirk, Wendy Rahn, Bruce Russett, and Beth Simmons._x000B_